2011
DOI: 10.1007/s00216-011-4791-z
|View full text |Cite
|
Sign up to set email alerts
|

Determination of gallium originated from a gallium-based anticancer drug in human urine using ICP-MS

Abstract: Urine analysis gives an insight into the excretion of the administered drug which is related to its reactivity and toxicity. In this work, the capability of inductively coupled plasma mass spectrometry (ICP-MS) to measure ultratrace metal levels was utilized for rapid assaying of gallium originating from the novel gallium anticancer drug, tris(8-quinolinolato)gallium(III) (GaQ(3)), in human urine. Sample dilution with 1% (v/v) HNO(3) as the only required pre-treatment was shown to prevent contamination of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…The urinary excretion of gallium following anticancer treatment by tris(8-quinolinolato)gallium(III) was studied by Filatova et al 302 In their investigation they have identified a couple of polyatomic or doubly charged ions interfering with both isotopes of Ga ( 69 Ga 1 and 71 Ga 1 ) such as 36 Ar 35 Cl 1 , 40 Ar 31 P 1 and 138 Ba 21 , but they could be separated by ICP-SFMS.…”
Section: Elemental Analyses Of Body Tissues and Body Fluidsmentioning
confidence: 98%
“…The urinary excretion of gallium following anticancer treatment by tris(8-quinolinolato)gallium(III) was studied by Filatova et al 302 In their investigation they have identified a couple of polyatomic or doubly charged ions interfering with both isotopes of Ga ( 69 Ga 1 and 71 Ga 1 ) such as 36 Ar 35 Cl 1 , 40 Ar 31 P 1 and 138 Ba 21 , but they could be separated by ICP-SFMS.…”
Section: Elemental Analyses Of Body Tissues and Body Fluidsmentioning
confidence: 98%
“…Knowing the Ga/Hp labeling ratio provides an opportunity to determine the concentration of this protein (or protein/drug conjugates) in complex biological matrices by measuring the levels of Ga. Ga can be readily detected in a variety of [52,53]. Figure 5 shows a relevant region of the ICP mass spectrum of a blank (human serum that had not been doped with Ga in any form), where low-abundance ionic signal is observed at both m/z 69 and 71, even though the measurements were carried out in the kinetic energy discrimination (KED) mode to reduce polyatomic interferences.…”
Section: Icp-ms Detection Of Hp·hb Ga In Human Serummentioning
confidence: 99%
“…In testing the solubility of GaQ 3 in simulated intestine juice, the blank signal at the mass of gallium-71 isotope was observed using high-resolution ICP-MS and attributed to the formation of 36 Ar 35 Cl + and 40 Ar 31 P + ions. 18…”
Section: Solubility Testingmentioning
confidence: 99%